Parental control and adolescent internet addiction: the moderating effect of parent-child relationships - Zhu, Xiaoqin; Deng, Chen; Bai, Wanyue (Frontiers in Public Health, 2023)
Introduction The present study investigated how maternal and paternal controls, including behavioral and psychological controls, predict adolescent Internet addiction, as well as the potential moderating effects of adolescent gender and parent-child relationships on the predictions. Methods Data were collected from 1,974 Chinese adolescents (age range = 14–22; mean = 16.47; SD = 0.87; 1,099 girls) in Guizhou Province, mainland China in November 2021. Internet addiction was measured using the ten-item Internet Addiction Test developed by Kimberly Young, and Parental control and parent-child relationships were measured by the respective subscales derived from the validated Chinese Parent-Child Subsystem Quality Scale. Results Hierarchical regression analyses revealed that after the covariates were statistically controlled, both parents' behavioral controls showed significant negative predictions on adolescent Internet addiction, while their psychological control tended to positively predict Internet addiction among adolescents, although the effect was only marginal. In addition, the impacts of maternal and paternal controls were equal, and such impacts did not vary between sons and daughters. While adolescent gender was not a significant moderator, the parent-child relationship quality significantly moderated the effects of paternal behavioral control, paternal psychological control, and maternal psychological control on adolescents' Internet addiction. Specifically, the prediction of paternal behavioral control was stronger while the effect of paternal and maternal psychological control was weaker among adolescents with a positive father-child relationship than those with a moderate or poor father-child relationship. Discussion These findings indicate the protective function of parents' behavioral control and the negative impact of psychological control on the development of adolescent Internet addiction. Further, a positive relationship between the father and the adolescent can strengthen the positive effect of paternal behavioral control and mitigate the negative effects of both parents' psychological controls.